Memórias de infância, relações de gênero e sexualidade nos significados e narrativas de professores/as - Cespedes, Cristiane Rojas (2015)
The school has a strategic role in the construction of meanings that guarantee the fairness and the right to a more humane and just education, including with regard to discussions of gender issues from kindergarten. This topic has generated discomfort and insecurity on the part of education professionals, since talking about sexuality is still not a priority in schools and kindergartens and therefore this issue has not permeated the pedagogical political projects. There is a denial of the sexuality of children and the avoidance of events that may occur in this context. The concept of heteronormativity and sexual repression are present in the discourse not only of children but also of / from teachers / as, which can perpetuate ideas that do not allow different ways of being a boy and being a girl and people live their sexuality. Thus, it is necessary to understand, discuss, reflect and create methodologies that effectively meet the current requirements in the face of issues related to sexuality in the experiences of children. This research aims to understand the meanings that / the teacher / the attribute to gender relations and sexuality from the experiences built at school in their life histories and interactions established with the children in their everyday teaching activities, as manifested in their narratives. In its practices, / the educators / as bring different views on sex education and many still feel unprepared, unable to speak openly about the subject, even though aware that, for psychological training, the social and cultural children, it is necessary consider the experiences, knowledge and ways of relating to one's own body and the body of another, as manifested by them. The research subjects are two teachers and two teachers working in early childhood education and the second cycle of primary education in schools of public networks of state and municipal school in Rondonópolis, Mato Grosso. The different moments of childhood schooling in which they operate and the fact that it is the study men and women participants are selection criteria of these subjects in the context of this investigation. This research is methodological bias oral history, focusing on narrative (auto) biographical. The narratives are marked by a process of reflection that takes each participant to reframe your life, memories and stories anchored in a specific theme: the experiences with sexuality and lived gender relations at school. The narratives of the stories experienced in childhood teachers and teachers are re-signified from the school everyday situations that bring children's experiences - his / her pupils / the - focused on gender relations and sexuality. Based on the analysis, the importance of education work and discuss issues of sexuality and gender relations with children is evident, adolescents and young people, breaking with disciplinary perspectives, normative, binary, guided in innocence as the essence of childhood and Body only treated as a gift of nature.